The Citrulline Recycling Pathway Sustains Cardiovascular Function in Arginine-Depleted Healthy Mice, but Cannot Sustain Nitric Oxide Production during Endotoxin Challenge. Issue 6 (7th June 2018) - Yuan, Yang; Mohammad, Mahmoud A; Betancourt, Ancizar; Didelija, Inka C; Yallampalli, Chandrasekar; Marini, Juan C
Abstract: Background: The recycling of citrulline by argininosuccinate synthase 1 (ASS1) and argininosuccinate lyase (ASL) is crucial to maintain arginine availability and nitric oxide (NO) production. Pegylated arginine deiminase (ADI-PEG20) is a bacterial enzyme used to deplete circulating arginine. Objective: The goal of this research was to test the hypothesis that citrulline is able to sustain intracellular arginine availability for NO production in ADI-PEG20 arginine–depleted mice. Methods: Six- to 8-wk-old male C57BL/6J mice injected with ADI-PEG20 (5 IU) or saline (control) were used in 4 different studies. Arginine, citrulline, and NO kinetics were determined by using stable isotopes in unchallenged (study 1) and endotoxin-challenged (study 2) mice. Blood pressure was determined by telemetry for 6 d after ADI-PEG20 administration (study 3), and vasomotor activity and ASS1 and ASL gene expression were determined in mesenteric arteries collected from additional mice (study 4). Results: ADI-PEG20 administration resulted in arginine depletion (<1 compared with 111 ± 37 µmol/L) but in greater plasma citrulline concentrations (900 ± 123 compared with 76 ± 8 µmol/L; P < 0.001) and fluxes (402 ± 17 compared with 126 ± 4 µmol ⋅ kg −1 ⋅ h −1 ; P < 0.001) compared with controls. Endotoxin-challenged ADI-PEG20–treated mice produced less NO than controls (13 ± 1 compared with 27 ± 2 µmol ⋅ kg −1 ⋅ h −1 ; P < 0.001). No differences ( P > 0.50) were observed for cardiovascular variables (heart rate, blood pressure) between ADI-PEG20–treated and control mice. Furthermore, no ex vivo vasomotor differences were observed between the 2 treatments. ADI-PEG20 administration resulted in greater gene expression of ASS1 (∼3-fold) but lower expression of ASL (–30%). Conclusion: ADI-PEG20 successfully depleted circulating arginine without any effect on cardiovascular endpoints in healthy mice but limited NO production after endotoxin challenge. Therefore, the citrulline recycling pathway can sustain local arginine availability independently from circulating arginine, satisfying the demand of arginine for endothelial NO production; however, it is unable to do so when a high demand for arginine is elicited by endotoxin.